(untitled) (Моделювання, керування та інформаційні технології, 2025)
The article investigates the total water consumption of rice in the Danube Delta over six growing seasons. The study established that the average water use amounts to 9,273 m³/ha, of which more than 50% is attributed to transpiration. A comparative analysis of the Alpatyev, Blaney–Criddle, and Hargreaves methods was carried out. The Alpatyev method proved to be the most accurate (error ±1.6%), while the Blaney–Criddle method is suitable for integral assessments, and the Hargreaves method is applicable only for preliminary calculations. The obtained results can be used to optimize irrigation regimes in rice systems of southern Ukraine.